Bacterial translocation and its reasons upper gastrointestinal endoscopy - Ömer GÜNAL; Lütfi DEĞİRMENCİOĞLU; Uğur ÇAŞKURLU; Gülperi KIVANÇ; Mustafa SÜMBÜL (Turkish Journal of Gastroenterology, 2019)
-